The Influence of Study-Abroad Experiences On Chinese College EFL Teacher’s Identity - Zhao, Yan; Mantero, Miguel (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
The purpose of this study was to explore how in-service Chinese college English teachers produce and reproduce their identities within their study-abroad experiences in terms of their beliefs and classroom practice. Sociocultural theory, discourse theory, and activity theory were used in the theoretical framework to analyze how participants modified their self-perception and changed their classroom practice in different contexts during boundary crossing. The study invited four in-service Chinese college English teachers who took part in three-month study-abroad program. Data were collected from interviews, observations, and document analysis. The findings indicated that participants shifted their self-perception from advanced language user to basic language learner when they studied abroad and had difficulty in dealing with daily tasks. With deeper involvement in the U.S. American culture, they gained more confidence in teaching. After they returned, they were more creative and critical teachers. The findings also demonstrated that participants wanted to implement the latest pedagogies, activities, and management into their own classrooms based on their students’ needs and levels in the Chinese sociocultural context. Although participants encountered challenges in implementation due to students’ levels, learning habits, and local context, they made some effective changes and formed new authority in the classroom. This study suggests that in order to improve study-abroad programs into truly beneficial professional development for teachers, college teachers need to have a clear self-evaluation process, and institutional administrators and foreign directors of study-abroad programs need to stand in teachers’ shoes to meet their requirements. This, in turn, will bring more Chinese college English teachers to study abroad for professional development.